Effect of leaf‐to‐fruit ratios on phenolic and sensory profiles of Malbec wines from single high‐wire‐trellised vineyards - Ahumada, Gastón E. (2020)
BACKGROUND: The single high‐wire system is a free canopy trellis system suitable for warm to hot climates. In a global warming scenario, it arouses as a technological solution since it prevents berry overheating and sunburn. Canopy management practices manipulate leaf‐to‐fruit ratios, affecting berry and wine composition. We aimed to evaluate the phenolic and sensory profiles of Malbec wines from single high‐wire trellised vineyards in a hot region in Mendoza (Argentina) and to assess the effect of varying leaf‐to‐fruit ratios on these attributes. We manipulated leaf‐to‐fruit ratios by varying shoot trimming (experiment 1: 0.45 m, 0.80 m, and untrimmed) and winter pruning severity (experiment 2: 16, 24, 32, and >32 countable buds per meter). We characterized wine attributes by a descriptive analysis, color by the CIELAB space, and global phenolics compounds and anthocyanins by high‐performance liquid chromatography with diode array detection. RESULTS: We found that wines where shoots were trimmed to 0.80 m or left untrimmed had similar and greater intensity of color, violet hue, astringency, and alcohol and a richer aroma profile than wines where shoots were trimmed to 0.45 m. Meanwhile, wines from 16 and >32 buds/m treatments (the latter simulating a box pruning) were similar to each other and had higher color intensity, violet hue, acidity, alcohol, and astringency and a more complex aroma profile than the other pruning treatments. CONCLUSIONS: The best quality wines were achieved by leaving 16 or >32 buds/m and by trimming shoots to 0.80 m or leaving them untrimmed. The modulation of cultural practices in sprawling canopies offers the potential to produce wines with different styles in hot regions.